A calculation method of earth pressure on sheeting between two piles considering soil arching effect and intermediate principal stress - Jinglin YOU; Shijie WANG; Haolan WANG (Shuiwen dizhi gongcheng dizhi, 2022)
The classical theories of earth pressure are based on the M-C strength criterion, which do not consider the influence of soil arching effect and intermediate principal stress on earth pressure, so the theoretical earth pressures are significantly larger than the actual values. In this respect, the existing research results also cannot consider the impact of both. In order to consider the comprehensive effect of soil arching effect, intermediate principal stress and soil cohesion on the earth pressure on the sheeting between two piles, the unified strength theory is used to analyze the strength of soil arching between piles, and a new method for calculating the earth pressure on the sheeting between piles is derived. In addition, based on the relationship between the Lode parameters and strain types, a practical calculation method of the unified strength index \begin{document}${φ _{\text{t}}}$\end{document} is proposed. Finally, combined with an engineering example, the calculated results are compared with the existing research results and the earth pressure determined by using the current code. The results indicate that the total active earth pressure calculated with this method is about 1/3~1/2 of that calculated by the traditional Rankine theory under the condition of different b values, and it is in accordance with the distribution law of the measured earth pressure. The research results are of important theoretical significance and practical value for the optimal design of pile-sheet retaining and the reduction of engineering cost.